Dilema Peliputan Terorisme dan Pergeseran Pola Framing Berita Terorisme di Media Massa - Adam W. Sukarno (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2011)
News about terrorism appears to be a hot topic in the media. However, the issue of terrorism is still a debate when it appeared in the news room. The issue is related to truth and objectivity of information. Accuracy of information in the process of news coverage in the media were key in putting a story viewed objectively. This article discusses the dilemma faced by journalist in reporting about terrorism and changing pattern of framing of news on terrorism in the mass media.